Seismic Facies of Pleistocene–Holocene Channel-fill Deposits in Bawean Island and Adjacent Waters, Southeast Java Sea - Ali Albab; Noor Cahyo Dwi Aryanto (Marine Geological Institute of Indonesia, 2017)
The late Pleistocene-Holocene stratigraphic architecture of the Bawean Island and surrounding waters, southeast Java Sea has been analyzed by using sparker seismic profiles. Geological interpretation of these seismic profiles revealed the widespread distribution of paleochannels with different shape and size in the present-day Java Sea. Two channel types can be distinguished based on its morphology: U-shaped channels in the western part and V-shaped channels in the eastern part. The stratigraphic successions were grouped into two major seismic units separated by different seismic boundaries. Characters of marine and fluvial deposits were determined based on seismic boundaries and internal reflectors. Three seismic facies can be identified within late Pleistocene – Holocene incised channel fills associated with SB2. The internal structure of incised-channels consist of chaotic reflector at the bottom, covered by parallel–sub parallel and almost reflection-free indicating the homogenous sediment deposited during the succession.Keywords : Pleistocene-Holocene channel fills, sparker seismic profiles, seismic boundaries, incised–channel, Java Sea. Rekaman seismik sparker digunakan untuk menganalisis endapan stratigrafi berumur Plistosen Akhir–Holosen di Perairan Pulau Bawean dan sekitarnya. Berdasarkan interpretasi geologi dari rekaman seismik tersebut teridentifikasi sebaran alur purba yang berbeda bentuk dan ukuran dengan kondisi Laut Jawa sekarang. Berdasarkan morfologinya, dua tipe alur purba yang terdentifikasi adalah alur purba berbentuk U di bagian barat dan berbentuk V yang terbentuk di bagian timur daerah penelitian. Suksesi stratigrafi kemudian dibedakan menjadi dua grup unit seismik utama yang dibatasi oleh perbedaan batas seismik, yaitu endapan asal darat dan laut yang ditentukan berdasarkan batas sikuen dan reflektor internal. Pada unit Pleistosen–Holosen teridentifikasi tiga tipe fasies seismik yang berkorelasi pada batas sikuen SB2. Struktur internal alur purba yang tertoreh terdiri dari reflektor kaotik yang di bagian bawah, kemudian ditutupi oleh reflektor paralel - sub paralel sampai hampir bebas refleksi yang mengindikasikan terendapkannya sedimen homogen selama suksesi tersebut.Kata kunci : Pengisi alur Plistosen - Holosen, penampang seismik sparker, batas seismik, alur tertoreh, Laut Jawa.